Academic Adaptation Among Students of Zakho University and Its Relationship with Some Demographic Variables - Bewar Taha Shukri; Mohammed Sadik Mohammed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
The aim of the current research is to identify the level of academic adaptation among the students of Zakho University, and the significance of the differences in their academic adaptation according to the demographic variables: (gender, academic grade, and specialization). The sample consisted of (750) male and female students who were chosen in a stratified random manner from the colleges affiliated to the University of Zakho. The researchers relied on the academic adaptation scale that was prepared, which consisted of (38) items distributed on four dimensions. Indicators of the scale's validity and reliability were confirmed. The data were treated statistically using the arithmetic means and standard deviations, in addition to using the t-test for one sample and for two independent samples. The results indicated that the students of the University of Zakho enjoyed a high level of academic adaptation, and it was found that there was a significant difference in the level of academic adaptation among the students of the University of Zakho due to the college variable, and the difference was in favor of the humanities majors, while no significant differences appeared in the academic adaptation according to the variables of gender and academic grade. A number of recommendations and proposals were presented in the light of the results of the research.